Low Heat of Adsorption of Ethylene Achieved by Major Solid‐State Structural Rearrangement of a Discrete Copper(I) Complex. (15th November 2018) - Jayaratna, Naleen B.; Cowan, Matthew G.; Parasar, Devaborniny; Funke, Hans H.; Reibenspies, Joseph; Mykhailiuk, Pavel K.; Artamonov, Oleksii; Noble, Richard D.; Dias, H. V. Rasika
Abstract: The trinuclear copper(I) pyrazolate complex [Cu3 ] rearranges to the dinuclear analogue [Cu2 ⋅(C2 H4 )2 ] when exposed to ethylene gas. Remarkably, the [Cu3 ]↔[Cu2 ⋅(C2 H4 )2 ] rearrangement occurs reversibly in the solid state. Furthermore, this transformation emulates solution chemistry. The bond‐making and breaking processes associated with the rearrangement in the solid‐state result in an observed heat of adsorption (−13±1 kJ mol −1 per Cu–C2 H4 interaction) significantly lower than other Cu–C2 H4 interactions (≥−24 kJ mol −1 ). The low overall heat of adsorption, "step" isotherms, high ethylene capacity (2.76 mmol g −1 ; 7.6 wt % at 293 K), and high ethylene/ethane selectivity (136:1 at 293 K) make [Cu3 ] an interesting basis for the rational design of materials for low‐energy ethylene/ethane separations.